Conocimientos y prácticas de bioseguridad en la administración de medicamentos por vía intravenosa por enfermeras de medicina interna y cirugía del Hospital Isidro Ayora - Luzuriaga Herrera, Cynthia Katherine (2015)
This research is a descriptive cross-sectional study, quantitative approach to describe the knowledge of nurses on biosecurity measures in the administration of intravenous medications in Internal Medicine and Surgery of the Hospital "Isidro Ayora" Loja. The universe was composed of 15 nurses working in Internal Medicine and Surgery. When applying the instrument to 12 nurses because 3 of them were on vacation was performed. The techniques used were: observation and survey of 6 questions developed based on the study variables, tabulation and analysis of data was performed using the frequency tables; determined that 100% of the nurses if they know about biosecurity measures in the administration of intravenous medications. In the application of biosecurity techniques, we observed that 58% wash their hands before and after each procedure and 42% is done before; 36% do not use gloves, only used for handling contaminated patients, 33% used a pair of gloves for all patients and 31% used a pair of gloves per patient. As for aseptic drug administration intravenously, 100% wash their hands before and after administering and change the peripheral venous catheter every 72 hrs or PRN, 86% perform disinfection puncture site, the 58% handled with aseptic technique medication, 33% used a syringe for each patient and 58% classified material used; perform aseptic and peripheral venous access care often by 58% and 42% do so rarely, 100% always label the peripheral venous catheter, classified and properly discard the material used; these services have and use the materials to administer medication. Upon completion of the investigative work is believed pertinent to the following recommendation: biosafety department Hospital Isidro Ayora continue to develop training to staff working in the institution on biosecurity and classification of the material used by educational talks, to thereby reduce transmission of infections and accidents. Keywords: Knowledge, practice nurse, administration, drugs intravenously.